Jan Amos Comenius: Timeless Pedagogy and Modernity (The Peerian Journal, 2024)
This article is about the pedagogical rules of the famous teacher John Amos Comenius and their practical application. The seven rules of pedagogy of a scientist and their significance in the methodology of Uzbek literature are discussed. Possible methodological approaches to each pedagogical rule are described. At the same time, certain recommendations are given for teaching Uzbek literature